Active Surveillance for Papillary Thyroid Microcarcinoma: Challenges and Prospects - Xue, Shuai; Wang, Peisong; Hurst, Zachary A.; Chang, Yi Seok; Chen, Guang (Frontiers in Endocrinology, 2018)
Abstract: Active surveillance (AS) can be considered as an alternative to immediate surgery in low-risk papillary thyroid microcarcinoma (PTMC) without clinically apparent lymph nodes, gross extrathyroidal extension (ETE), and/or distant metastasis according to American Thyroid Association. However, in the past AS has been controversial, as evidence supporting AS in the management of PTMC was scarce. The most prominent of these controversies included, the limited accuracy and utility of ultrasound (US) in the detection of ETE, malignant lymph node involvement or the advent of novel lymph node malignancy during AS, and disease progression. We summarized publications and indicated: 1): US, performer-dependent, could not accurately diagnose gross ETE or malignant lymph node involvement in PTMC. However, the combination of computed tomography (CT) and US provided more accurate diagnostic performance, especially in terms of selection sensitivity. 2): Compared to immediate surgery patients, low-risk PTMC patients had a slightly higher rate of lymph node metastases, although the overall rate for both groups remained low. 3): Recent advances in the sensitivity and specificity of imaging and incorporation of diagnostic biomarkers have significantly improved confidence in the ability to differentiate indolent versus aggressive PTMCs. Our paper reviewed current imagings and biomarkers with initial promise to help select AS candidates more safely and effectively. These challenges and prospects are important areas for future research to promote AS in PTMC.